Neurodidactics for a culture of kindness - Tinoco Tinoco, Wilson Alcivar; Lalangui Sarango, Ricardo Geovanni; Jaramillo Aguilar, Betty Azucena (SATHIRI, 2022)
The present research is intended to highlight the importance of neurodidactics, especially in terms of emotions and their incidence on learning. As well as to understand that it is necessary to educate for a culture with good practices that begins with the value of the person without distinction of his condition or origin and considering his fundamental aspects of life such as the material, somatic, psychological, and spiritual. The research approach is mixed, not experimental, it is bibliographic, descriptive, and field in nature. To obtain the empirical information, a survey, based on a questionnaire of six questions, was applied to the whole teaching population of “Combate de Pilo” School and “Matilde Hidalgo de Procel” High School, both public institutions in Machala city, El Oro Province. This information allowed to conclude that respondents showed serious problems in terms of knowledge of neurodidactics. Most of them (82.36%) believed that it is a contribution of pedagogues and teachers, which is false because this is a benefit of the neuroscience. Likewise, it was detected that educators gave importance to emotions, there is even an adherence. They assured that it is decisive to achieve a cultural change, but they denied when informing that “doing good” consists on improving people’s material conditions and food. These variations denoted that something is happening on teachers’ training. Therefore, it is recommended to create opportunities for pedagogical instruction, self-preparation, reflection on teaching practice, and spiritual growth.